Thalassaemia screening among healthy blood donors in Hospital Tengku Ampuan Rahimah, Klang. - Ezalia E,; Irmi Elfina R,; G, Elizabeth; Wan Hayati MY,; Norhanim A,; Wahidah A,; Chin, YM; Rahimah A,; Nor Asiah M,; Masita A,; Rohaidah H,; Zubaidah Z, (Penerbit UKM, 2014)
Thalassaemia screening programme has been conducted in Malaysia since 2004. The aim of the programme was to reduce the burden of the disease by identifying thalassaemia carriers. However, the response towards the screening activities was unsatisfactory as there was lack of public awareness against the importance of thalassaemia screening. An alternative approach is to screen blood donors. The purpose of this study was to observe the prevalence of thalassaemia carriers among healthy blood donors. Seven hundred and thirty eight healthy blood donors were screened in Hospital Tengku Ampuan Rahimah, Klang from July to September 2010 using cation-exchange high performance liquid chromatography (HPLC). Cases with haemoglobin variants were further analyzed by gel electrophoresis at alkaline pH. Result shows that the blood donors consisted of 413 Malays (56%), 162 Indians (22%), 148 Chinese (20%) and 15 others (2%). There were 19 (2.6%) individuals with haemoglobin E trait, six (0.8%) with co-inheritance of haemoglobin E and αα-thalassaemia and five (0.7%) with β-thalassaemia trait. Haemoglobin Constant Spring and haemoglobin A2 prime were observed in two (0.3%); and Haemoglobin Lepore and alpha chain variant in one (0.2%). αα-thalassaemia and normal haemoglobin A2 β-thalassaemia could not be excluded in 190 cases (26%), as they required deoxyribonucleic acid (DNA) studies for identification. Thalassaemia screening in blood donors is more feasible and effective. Therefore, a wider scale population screening including blood donors could benefit the existing thalassaemia screening programme in Malaysia.